2014
DOI: 10.1039/c4cc00967c
|View full text |Cite
|
Sign up to set email alerts
|

Applying a multitarget rational drug design strategy: the first set of modulators with potent and balanced activity toward dopamine D3 receptor and fatty acid amide hydrolase

Abstract: Combining computer-assisted drug design and synthetic efforts, we generated compounds with potent and balanced activities toward both D3 dopamine receptor and fatty acid amide hydrolase (FAAH) enzyme. Concurrently modulating these targets, our compounds hold a great potential toward exerting a disease-modifying effect on nicotine addiction and other forms of compulsive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The results obtained are reported in Tables and for series I and II, respectively. Regarding series I, (Table ) compound 5 , with an unsubstituted 2‐oxo‐benzimidazole core, was a potent D3R modulator with an EC 50 value of 7.9 nM; molecular modelling studies showed as it simultaneously engaged both the OBP and the SBP (Figure A), in line with previously reported simulations . At GSK‐3β, 5 showed an IC 50 value of 20.1 μM; the 2‐oxo‐benzimidazole moiety engaged the hinge region of the enzyme, forming the typical H‐bond pattern of kinase inhibitors, while the arylpiperazine group projected outside the pocket (Figure B).…”
Section: Figuresupporting
confidence: 82%
“…The results obtained are reported in Tables and for series I and II, respectively. Regarding series I, (Table ) compound 5 , with an unsubstituted 2‐oxo‐benzimidazole core, was a potent D3R modulator with an EC 50 value of 7.9 nM; molecular modelling studies showed as it simultaneously engaged both the OBP and the SBP (Figure A), in line with previously reported simulations . At GSK‐3β, 5 showed an IC 50 value of 20.1 μM; the 2‐oxo‐benzimidazole moiety engaged the hinge region of the enzyme, forming the typical H‐bond pattern of kinase inhibitors, while the arylpiperazine group projected outside the pocket (Figure B).…”
Section: Figuresupporting
confidence: 82%
“…Hek293 cells stably transfected with the h-FAAH-1 were used as enzyme source. The fluorescent assay to measure FAAH-1 activity was performed as previously described by De Simone et al [69].…”
Section: Fluorogenic H-faah1 In Vitro Assaymentioning
confidence: 99%
“…We exploited a ligand-based approach by combining the pharmacophoric features responsible for binding to BACE-1 and GSK-3b, such as a guanidino motif and a cyclic amide group, respectively, into a single scaffold ( Figure 1). We subsequently performed structure-based docking simulations [15] to study the interactions of triazinonebased compounds with the catalytic pocket of both enzymes ( Figure 2). We subsequently performed structure-based docking simulations [15] to study the interactions of triazinonebased compounds with the catalytic pocket of both enzymes ( Figure 2).…”
mentioning
confidence: 99%